The World He Sought: Nazrul in Coolies and Laborers - Langley , Winston E. (Journal of Ethnic and Cultural Studies, 2023)
Kazi Nazrul Islam, the national poet of Bangladesh, envisioned a future possibility for humankind, a community of care. The dominant socio-economic and political thinking of this century, however, finds his vision and unrealizable dream, especially in the light of the cleavages that wall human groupings from another—ethnicity, gender, geography, language, nationality, race, religion, and social class, among others. The focus of this article is to show that the dream has been informing some of the thinking of the last and present century, from a variety of cultural traditions, and that its policy implications, through a number of forums, including the United Nations, offer a future within which the entire human species, together, and the Earth, can mutually thrive and grow.